EMOTIONAL INTELLIGENCE a simple and actionable guide to increasing performance, engagement and... ownership. - JACOBSON, AMY (JOHN WILEY & SONS AUSTRAL, 2020)
Boost Emotional Intelligence in any situation to achieve exceptional results for any organisation As organisations around the world are putting more focus on the mindset and wellbeing of staff, the need to develop Emotional Intelligence (EI) has never been greater. Emotional Intelligence in the workplace--including the five key concepts of self-awareness, self-regulation, empathy, social skills and motivation--is defined as your ability to identify and manage your personal emotions and the emotions of your colleagues and co-workers. Emotional Intelligence is in high demand and is expected to become an essential component of success in the future of work. Emotional Intelligence: A Simple and Actionable Guide to Increasing Performance, Engagement and Ownership is designed to help you master EI and empower you to achieve the very best outcome for everyone in your organisation. Cutting through the hype and dispelling the myths about EI, this practical, easy-to-use resource provides clear guidance, powerful tools, and actionable steps for developing and implementing EI in the workplace for immediate results. Amy Jacobson, an experienced EI specialist, leadership trainer and coach, shares the tools, methodologies, concepts and actions that increase EI in any situation. Packed with real-life examples and case studies, insightful questions, and useful diagrams to create action, this must-have guide: Offers a powerful 5-part methodology--Own It, Face It, Feel It, Ask It, and Drive It--to help you understand and immediately implement Emotional Intelligence principles in both your personal and professional life Increases your Emotional Intelligence in the workplace to enable you to inspire and energise staff, support empathy and self-awareness, and drive high levels of performance Improves the way you handle high pressure environments, manage challenging situations, and interact with people with different communication styles Helps you solve difficult problems in the workplace such as loss of purpose and engagement, cultural issues, poor communication, and low productivity Provides concrete steps for eliminating negative behaviors and for owning the role you play, your impact on others, and the decisions and choices you make Emotional Intelligence: A Simple and Actionable Guide to Increasing Performance, Engagement and Ownership is an indispensable book for anyone interacting with others in the workplace, especially those with leadership roles such as senior executives, board members, department heads, managers and supervisors.